Compacton and periodic wave solutions of the non-linear dispersive Zakharov-Kuznetsov equation - İnç, Mustafa (De Gruyter Poland Sp Z O O, 2007)
In this paper, the nonlinear dispersive Zakharov-Kuznetsov equation is solved by using the sine-cosine method. As a result, compactons, periodic, and singular periodic wave solutions are found. (c) Versita Warsaw and Springer-Verlag Berlin Heidelberg. All rights reserved.
Keywords: Zakharov-Kuznetsov equation; compacton; periodic wave solution